2019
DOI: 10.1371/journal.pntd.0007594
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide survey of Leishmania infantum infection in cats and associated risk factors in Italy

Abstract: Though scantly investigated, Leishmania infantum infection and clinical cases of leishmaniasis in cats have been recently reported in several countries of the Mediterranean basin, with large variability in prevalence data. A major limitation in the comparability of the data available is attributed to the differences in diagnostic techniques employed and cat populations sampled. The aim of this study was to assess the prevalence of L . infantum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
60
5
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 44 publications
14
60
5
3
Order By: Relevance
“…FIV serology was positive in 7% of the cats and no statistically significant association was found between FIV and L. infantum infections. Some other studies on large numbers of cats in Italy and Brazil have found an association between feline leishmaniosis and FIV [17,18] whereas studies from Spain and Cyprus failed to find such an association [19,20]. It is likely that an association between FIV and L. infantum infection was not found in the present study due to the small number of FIV-positive cats detected in the shelter and the overall limited feline population size evaluated.…”
Section: Discussioncontrasting
confidence: 68%
“…FIV serology was positive in 7% of the cats and no statistically significant association was found between FIV and L. infantum infections. Some other studies on large numbers of cats in Italy and Brazil have found an association between feline leishmaniosis and FIV [17,18] whereas studies from Spain and Cyprus failed to find such an association [19,20]. It is likely that an association between FIV and L. infantum infection was not found in the present study due to the small number of FIV-positive cats detected in the shelter and the overall limited feline population size evaluated.…”
Section: Discussioncontrasting
confidence: 68%
“…Most of the literature generated on FeVBDs worldwide has been focussed on feline leishmaniosis in concomitant with viral infections by feline leukaemia virus (FeLV) and feline immunodeficiency virus (FIV) and on feline bartonellosis or haemoplasmosis [3,[12][13][14][15][16][17]. In contrast, a relative low number of studies were conducted on Rickettsia spp., Anaplasma spp., Hepatozoon spp.…”
Section: Introductionmentioning
confidence: 99%
“…infantum. Similarly, this picture has been suggested also for cats, which presumably act as reservoir hosts at least in endemic areas of zoonotic VL (Pennisi et al, 2018;Asfaram et al, 2019;Iatta et al, 2019).…”
Section: Discussionmentioning
confidence: 60%
“…In endemic areas, L. infantum is maintained by several mammal species in nature (Roque and Jansen, 2014) and the role of wildlife species (e.g., red fox, golden jackal, gray wolf, hare, black rat) has been suggested in a series of studies (Millan et al, 2014;Otranto et al, 2015). After being long regarded as resistant, cats have gain the interest of the scientific community as hosts of L. infantum, mainly in endemic areas (Iatta et al, 2019;Asfaram et al, 2019). Clinical signs compatible with feline leishmaniasis (FeL) include lymphadenomegaly, splenomegaly, weight loss, anorexia, as well as cutaneous, mucocutaneous and ocular lesions (Pennisi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%